2019
DOI: 10.19080/ctftte.2019.04.555646
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial finishes for Textiles

Abstract: Infestations by micro-organism instigate cross disease by pathogens and odor develops in fabric have direct contact with the skin. Moreover, discoloration, tints and loss of functional characteristics of textiles are consequence of microbial damage. Antibacterial finished textile is an important area for medical and hygienic applications and there is enormous need of non-toxic and eco-friendly antimicrobial agents. The synthetic biocides finishes extensively reported were polyhexamethylenebiguanide (PHMB), qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 35 publications
0
1
0
Order By: Relevance
“…Considering this, Ain Samat et al employed Citrus aurantifolia extract in the biosynthesis of zinc oxide (ZnO) nanoparticles. They used zinc acetate as the precursor of Zn at various concentrations, and they reported that the synthesized ZnO nanoparticles were between 50 and 200 nm in size using FESEM [5] Manal et al [70] attempted to synthesize Agnanoparticles using biological waste material from citrus lime peels, and to characterize the produced green Ag-nanoparticles for their antibacterial properties and cytotoxic effects. According to a UVvisible spectrophotometer analysis of the synthesized Ag-nanoparticles, spherical and irregularly agglomerated Ag-nanoparticles development was reported.…”
Section: Citrus Plants As Bio-reductants In Synthesis Of Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering this, Ain Samat et al employed Citrus aurantifolia extract in the biosynthesis of zinc oxide (ZnO) nanoparticles. They used zinc acetate as the precursor of Zn at various concentrations, and they reported that the synthesized ZnO nanoparticles were between 50 and 200 nm in size using FESEM [5] Manal et al [70] attempted to synthesize Agnanoparticles using biological waste material from citrus lime peels, and to characterize the produced green Ag-nanoparticles for their antibacterial properties and cytotoxic effects. According to a UVvisible spectrophotometer analysis of the synthesized Ag-nanoparticles, spherical and irregularly agglomerated Ag-nanoparticles development was reported.…”
Section: Citrus Plants As Bio-reductants In Synthesis Of Nanoparticlesmentioning
confidence: 99%
“…The demand for hygienic materials, such as biocidal coatings in textiles (sportswear, undergarments, and bedding linen), is escalating with the advancement of living standards. The antibacterial finishing treatments has become an essential aspect of medical, therapeutic, and healthcare practises due to various potentially infectious microorganisms in hospital environments that might cause cross-infection disorders [5]. Antimicrobial finishing is one of the most significant functional finishes applied to hospital textiles, as well as everyday garments.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the population of hospitals and nursing homes may be classified as vulnerable to microbial infections. Multidrug-resistant bacteria (MDRB) are among the major concerns of worldwide healthcare units since their growing prevalence represents a serious threat to the Sustainable Development Goals set by the World Health Organization (WHO) [1][2][3]. MDRB infections represent between 20 and 25% of cases in hospitals and approximately 17% in nursing homes [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, current viral pandemics and outbreaks represent a high concern in healthcare units, as some species can maintain viability for up to 60-140 days on soft surfaces subjected to repeated contact [6]. Therefore, textile materials may represent an important vehicle for the propagation of microorganisms, due to their high contact surface and capacity to retain moisture, creating a perfect environment for the maintenance and spreading of virus and bacteria [3,7,8]. This is particularly relevant in common comfort healthcare textiles ubiquitously present in hospitals and nursing centers, such as blankets.…”
Section: Introductionmentioning
confidence: 99%
“…The antimicrobial finishing process imparts the ability, to textile substrate, to inhibit the growth (-static) or reproduction of at least some types of microorganisms or to kill (-cidal) at least some types of microorganisms" [1][2][3]. Therefore, an antimicrobial finish should be capable to kill the microbes by breaching the cell wall or alter cell membrane permeability, obstructing the synthesis of proteins of microbes, blocking enzyme production necessary for microbes' food [1]. The major use of the antimicrobial was in the medical and the pharmaceutical industry.…”
Section: Introductionmentioning
confidence: 99%